HUBUNGAN ANTARA KEIKUTSERTAAN DALAM PROGRAM PENGEMBANGAN DAN KINERJA PROFESIONAL GURU - Rita Aprilianti Rukmana (Universitas Negeri Malang, 2017)
Abstract: This study aims to determine the relationship between participation in the development and professional performanceof vocational high school teacher in Malang City. This research using a quantitative correlation approach. the data was analyzed using Product Moment Pearson correlation. The findings show that: (1) participation teachers in the development program in the category often with the average score of 97.87; (2) the performance variables of teacher professional included in the medium category with an average score of 107.48 so included in the enough professional category; and (3) there variable correlation participation in program development and professional performance with a 0.366 correlation value is greater than 0,113. Thus it can be interpreted as the relationship between Participation in the Program Development and Professional Teachers Performance. Keywords: Development programme, Performance, Profesional teachers Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan antara keikutsertaan dalam program pengembangan dan kinerja profesional guru SMKN se-Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif korelasional. Data yang terkumpul dianalisis menggunakan uji korelasi Product Moment Pearson. Temuan penelitian menunjukkan, bahwa: (1) keikutsertaan guru dalam program pengembangan dalam kategori sering dengan skor rata-rata sebesar 97,87; (2) variabel kinerja profesional guru masukdalam kategori sedang dengan skor rata-rata 107,48 sehingga termasuk dalam kategori cukup profesional; dan (3) terdapat korelasi variabel keikutsertaan dalam program pengembangan dan kinerja profesional dengan nilai korelasi 0,366 lebih besar dari 0,113.Dengan demikian dapat dimaknai adanya hubungan antara Keikutsertaan dalam Program Pengembangan dan Kinerja Profesional Guru. Kata kunci: Program pengembangan, Kinerja, Profesional guru.   DOI: https://doi.org10.17977/um025v1i22017p107